2022
DOI: 10.3390/healthcare10050832
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Patterns and Factors Related to Sleep Disturbances in Prostate Cancer Patients

Abstract: Prostate cancer patients may experience disturbed sleep as a result of their diagnosis or treatment. This study sought to evaluate disturbed sleep and excessive daytime sleepiness in newly diagnosed patients and those receiving androgen deprivation therapy (ADT). This study was conducted with 74 patients. Subjective data using the Pittsburgh Sleep Quality Index (PSQI) and Epworth Sleepiness Scale (ESS) and actigraphy data on ADT/ADT-naïve patients were collected. The prevalence of poor sleep quality, determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…The collective use of actigraphy and subjective sleep questionnaires is both feasible and relatively inexpensive in a clinical setting to assess sleep profiles that can serve as a platform for conducting larger clinical trials. This has been corroborated in our own institutional feasibility study of 74 patients with prostate cancer [121].…”
Section: Discussionsupporting
confidence: 73%
“…The collective use of actigraphy and subjective sleep questionnaires is both feasible and relatively inexpensive in a clinical setting to assess sleep profiles that can serve as a platform for conducting larger clinical trials. This has been corroborated in our own institutional feasibility study of 74 patients with prostate cancer [121].…”
Section: Discussionsupporting
confidence: 73%
“…A scoping review which analyzed the prevalence of frailty syndrome in mPCa found that 70% of patients with mPCa were frailer than localized patients [27]. We also propose to evaluate the role of other geriatric variables such as depressive symptoms and insomnia, given that studies have linked androgen depletion to depressive symptoms and/or insomnia in men without prostate cancer [28][29][30][31] and in patients with prostate cancer [32][33][34]. Since frailty has been related to age, polypharmacy, and overweight, we also analyzed the contribution of these variables.…”
Section: Introductionmentioning
confidence: 99%